Limites de escala em modelos de armadilhas - Santos, Lucas Araújo (2015)
Let X = fX 0;X0 = 0g be a mean zero -stable random walk on Z with inhomogeneous jump rates f 1 i ; i 2 Zg, with 2 (1; 2] and f i : i 2 Zg is a family of independent random walk variables with common marginal distribution in the basis of attraction of an -stable law with 2 (0; 2]. In this paper we derive results about the long time behavior of this process, we obtain the scaling limit. To this end, rst we will approach probability on metric spaces, speci cally treat the D space of the functions that are right-continuous and have left-hand limits. We will also expose some results dealing with stable laws that are directly related to the above problem.